Herpes zoster vaccine: A health economic evaluation for Switzerland - Patricia R. Blank; Zanfina Ademi; Xiaoyan Lu; Thomas D. Szucs; Matthias Schwenkglenks (Taylor & Francis Group, 2017)
Herpes zoster (HZ) or "shingles" results from a reactivation of the varicella zoster virus (VZV) acquired during primary infection (chickenpox) and surviving in the dorsal root ganglia. In about 20% of cases, a complication occurs, known as post-herpetic neuralgia (PHN). A live attenuated vaccine against VZV is available for the prevention of HZ and subsequent PHN. The present study aims to update an earlier evaluation estimating the cost-effectiveness of the HZ vaccine from a Swiss third party payer perspective. It takes into account updated vaccine prices, a different age cohort, latest clinical data and burden of illness data. A Markov model was developed to simulate the lifetime consequences of vaccinating 15% of the Swiss population aged 65-79 y. Information from sentinel data, official statistics and published literature were used. Endpoints assessed were number of HZ and PHN cases, quality-adjusted life years (QALYs), costs of hospitalizations, consultations and prescriptions. Based on a vaccine price of CHF 162, the vaccination strategy accrued additional costs of CHF 17,720,087 and gained 594 QALYs. The incremental cost-effectiveness ratio (ICER) was CHF 29,814 per QALY gained. Sensitivity analyses showed that the results were most sensitive to epidemiological inputs, utility values, discount rates, duration of vaccine efficacy, and vaccine price. Probabilistic sensitivity analyses indicated a more than 99% chance that the ICER was below 40,000 CHF per QALY. Findings were in line with existing cost-effectiveness analyses of HZ vaccination. This updated study supports the value of an HZ vaccination strategy targeting the Swiss population aged 65-79 y.